BAURAN PEMASARAN GAS ELPIJI PADA PT.CITRA KARUNIA ILAHI BANJARMASIN - Widarto Widarto; M. Ridha Ansyari Rizky; Ade Hermawan; Riky Welli Saputra (Universitas Islam Kalimantan Muhammad Arsyad Al Banjari, 2022)
This study aims to determine the Marketing Mix (Product, Price, Distribution andPromotion) of LPG, to find out what obstacles are faced and what alternative solutionscan be done related to the constraints faced.This research uses a descriptive method. Sources of data used in this study are primarydata and secondary data. Data collection techniques used are through observation,interviews and documentation. The data analysis technique is descriptive qualitativedata analysis technique.The results showed that, the marketing mix carried out by PT. Citra Karunia Ilahi is theselection of products marketed, namely subsidized and non-subsidized LPG GasProducts. Non-subsidized LPG Gas products include 5.5 Kg LPG Gas, 12 KG LPG Gas,and 12 KG LPG Bright Gas, then the application of varying prices, for the price of 5.5Kg refill cylinders is priced at Rp. 65,000, LPG 12 Kg Rp. 142,000, and LPG 12 KgBright gas Rp. 145,000. PT. Citra Karunia Divine distributes Non-subsidized LPG GasProducts to gas stations, minimarkets, subsidized LPG Gas Bases, MSMEs, Institutionsand to the public directly, while the promotion is carried out by means of promotionsthrough banners/banners, and promotions for holidays. The obstacles faced are the lackof purchasing power and public interest in non-subsidized LPG Gas, and the PromotionStrategy is still not intensive, while the Alternative Solution that can be applied is byconducting a tube loan trial program, and using Digital Marketing and Promotionstrategies.